2001
DOI: 10.4049/jimmunol.167.6.3300
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Mediated Killing of Intracellular Mycobacteria by Macrophages Is a P2X7-Dependent Process Inducing Bacterial Death by Phagosome-Lysosome Fusion

Abstract: Mycobacterium tuberculosis survives within host macrophages by actively inhibiting phagosome fusion with lysosomes. Treatment of infected macrophages with ATP induces both cell apoptosis and rapid killing of intracellular mycobacteria. The following studies were undertaken to characterize the effector pathway(s) involved. Macrophages were obtained from p47phox and inducible NO synthase gene-disrupted mice (which are unable to produce reactive oxygen and nitrogen radicals, respectively) and P2X7 gene-disrupted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
3
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(190 citation statements)
references
References 47 publications
4
181
3
2
Order By: Relevance
“…Classical activation of macrophages is intimately linked to induction of microbicidal activity and several studies have shown that P2X 7 R play a role in killing of Mycobacterium tuberculosis via activation of phospholipase D [8,9,35]. The down-regulation of surface P2X 4 R in classically activated alveolar macrophages makes it unlikely that P2X 4 R are involved in the killing of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Classical activation of macrophages is intimately linked to induction of microbicidal activity and several studies have shown that P2X 7 R play a role in killing of Mycobacterium tuberculosis via activation of phospholipase D [8,9,35]. The down-regulation of surface P2X 4 R in classically activated alveolar macrophages makes it unlikely that P2X 4 R are involved in the killing of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopy shows P2X7 in the phagosome membrane surrounding engulfed particles or bacteria [29,30] and recent reports suggest that P2X7 together with pannexin-1 may facilitate the delivery of bacterial products from phagosome lumen into the cytosol, where they can activate inflammasome assembly [31,32]. Moreover P2X7 has a role in facilitating the fusion of phagosome with lysosome by a process involving stimulation of phospholipase D activity presumably on the phagolysosomal membrane [33,34].…”
Section: Non-opsonized Beadsmentioning
confidence: 94%
“…Phospholipase D has been recently involved in ATPinduced killing of intracellular mycobacteria by human macrophages (Fairbairn et al ., 2001). Because macrophages show a different ability to control intracellular replication of pathogenic and non-pathogenic mycobacteria such as MTB and Msm, we tested the hypothesis that such differences in intracellular growth control could reflect differences in host PLD activity.…”
Section: Infection Of Human Macrophages With Pathogenic Mtb or Non-pamentioning
confidence: 99%
“…As the involvement of PLD activation has recently been shown in ATP-induced killing of intracellular mycobacteria (Fairbairn et al ., 2001) and we have shown that it is crucial in the control of Msm viability (Fig. 3), we investigated the enzyme role in CpG-induced MTB killing.…”
Section: Cpg Odn Induce Intracellular Mycobacterial Growth Control Thmentioning
confidence: 99%
See 1 more Smart Citation